Interaction of Amino Acid Schiff Base Metal Complexes with DNA/BSA Protein and Antibacterial Activity: Spectral Studies, DFT Calculations and Molecular Docking Simulations. (31st January 2018) - Neelakantan, M.A.; Balamurugan, K.; Balakrishnan, Chithiraivel; Subha, L.
Abstract : Cu(II), Ni(II) and Zn(II) complexes of (E)‐2‐((2, 4‐dihydroxybenzylidene)amino)‐3‐(1H‐indol‐3‐yl)propanoic acid Schiff base (L ) were synthesized and characterized by various spectral methods. ESI‐MS was used to confirm the structure of synthesized compounds. Molecular geometries of the complexes were predicted by optimizing the structure by DFT/B3LYP method with LANL2DZ basis set in the gas phase. The interaction of the metal complexes with CT‐DNA and BSA protein has been examined by UV‐vis, fluorescence and viscometer titrations reveal that the complexes bind to DNA through intercalation binding mode. The copper complexes exhibit effective cleavage of pUC19 DNA by the oxidative mechanism. The synthesized compounds screened for their antibacterial activities against various bacteria strains exhibit theL and copper complex show potential activity against Pseudomonas aeruginosa and Escherichia coli, respectively. Subsequently, molecular docking studies were performed on to understand the binding of the compounds with DNA, BSA and bacteria. Abstract : Cu(II), Ni(II) and Zn(II) complexes of (E)‐2‐((2, 4‐dihydroxybenzylidene) amino)‐3‐(1H‐indol‐3‐yl)propanoic acid Schiff base (L) were synthesized and characterized. DNA/BSA protein interactions of these metal complexes were evaluated.